2020
DOI: 10.1016/j.omtn.2020.09.020
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Silencing of lncRNA LINC00857 Enhances BIRC5-Dependent Radio-Sensitivity of Lung Adenocarcinoma Cells by Recruiting NF-kB1

Abstract: Lung adenocarcinoma (LUAD) is a predominant type of lung cancer in never-smoker patients. In this study, we identified a long noncoding RNA (lncRNA) LINC00857 that might regulate radio-sensitivity of LUAD cells. Expression of LINC00857 and baculoviral IAP repeat containing 5 (BIRC5) was determined to be upregulated in LUAD cells and tissues using qRT-PCR and western blot analysis. The correlation between LINC00857 and nuclear factor kappa B subunit 1 (NF-kB1) was verified using RNA immunoprecipitation and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…BIRC5 is also reported to be one of the prognostic markers for lung adenocarcinoma [ 21 ]. Moreover, BIRC5 up-regulation was previously documented in lung adenocarcinoma cells and tissues, wherein = radiosensitivity could affect the dependence on BIRC5 expression [ 11 ]. Consistently, RT-qPCR and Western blotting results in our study revealed that BIRC5 was highly-expressed in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BIRC5 is also reported to be one of the prognostic markers for lung adenocarcinoma [ 21 ]. Moreover, BIRC5 up-regulation was previously documented in lung adenocarcinoma cells and tissues, wherein = radiosensitivity could affect the dependence on BIRC5 expression [ 11 ]. Consistently, RT-qPCR and Western blotting results in our study revealed that BIRC5 was highly-expressed in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, MNPs further serve as contributors to nanotriggers, which possess the ability to control cell function [ 10 ]. On the other hand, Baculoviral IAP repeat containing 5 (BIRC5) is up-regulated in lung adenocarcinoma cells and tissues, wherein radiosensitivity was found to influence the dependance on BIRC5 expression [ 11 ]. Moreover, genes can be inhibited by antisense oligodeoxynucleotide (AS-ODN) or by small interference RNA (siRNA), and previously been highlighted as a promising treatment avenue for lung adenocarcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrantly activated dysregulation of lncRNAs and miRNAs has been elucidated to participate in pathogenesis, development, and metastasis in LUAD ( 9 ). In 2018, LINC00665 was initially identified as a lncRNA, which is highly overexpressed in hepatocellular carcinoma (HCC) and associated with poor progression in HCC patients ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a class of noncoding RNA transcripts that are more than 200 nucleotides in length, with no apparent protein-coding capacity ( 6 , 7 ). It is well known that the abnormal expression of lncRNAs in LUAD is widespread, which play critical roles in tumor initiation and progression ( 8 , 9 ). As an annotated human lncRNA, LINC00665 has been reported to occur primarily in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted using TRIzol reagent according to the Kit’s instructions. 22 RNA concentration was measured in a spectrophotometer, and the quality of all RNA samples was assessed by electrophoresis on 1.5% denaturing Agarose gels. 23 The mRNA libraries were separately generated from total RNA and constructed according to the standard Illumina RNA library preparation protocol (Illumina, USA).…”
Section: Methodsmentioning
confidence: 99%